2015
DOI: 10.1039/c5cp03028e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of CO2 to ethylene glycol on imidazolium ion-terminated self-assembly monolayer-modified Au electrodes in an aqueous solution

Abstract: Imidazolium ion-terminated self-assembled monolayer (SAM)-modified electrodes achieve CO2 conversion while suppressing hydrogen evolution. Immobile imidazolium ion on gold (Au) electrodes reduce CO2 at low overpotential. The distance between electrode and imidazolium ion separated by alkane thiol affects CO2 reduction activity. CO2 reduction current depends on the tunnel current rate. Although the product of CO2 reduction at the bare Au electrode is CO, SAM-modified electrodes produce ethylene glycol in aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 33 publications
0
68
0
Order By: Relevance
“…Over the past few decades,several catalyst materials with the capability of reducing CO 2 electrochemically in CO 2 saturated-aqueous solutions have been identified. [3,[7][8][9][10][11][12][13][14][15][16][17][18] It has been demonstrated that polycrystalline Au is capable of reducing CO 2 to CO with ah igh faradaic efficiency (FE) of about 87 %a tÀ0.74 vs.r eversible hydrogen electrode (RHE). [5] While Au is currently the most efficient electrocatalytic surface for CO 2 reduction to CO,the low abundance and high cost of Au may prevent its large-scale applications.…”
mentioning
confidence: 99%
“…Over the past few decades,several catalyst materials with the capability of reducing CO 2 electrochemically in CO 2 saturated-aqueous solutions have been identified. [3,[7][8][9][10][11][12][13][14][15][16][17][18] It has been demonstrated that polycrystalline Au is capable of reducing CO 2 to CO with ah igh faradaic efficiency (FE) of about 87 %a tÀ0.74 vs.r eversible hydrogen electrode (RHE). [5] While Au is currently the most efficient electrocatalytic surface for CO 2 reduction to CO,the low abundance and high cost of Au may prevent its large-scale applications.…”
mentioning
confidence: 99%
“…The use of ionic liquid (IL) based electrolytes for the reduction of CO 2 provides numerous advantages. Among these advantages are the impact on the overpotential, the competing hydrogen evolution reaction (HER), the product selectivity, and the product scope . Especially, ILs featuring imidazolium cations have emerged as versatile co‐catalysts.…”
Section: Introductionmentioning
confidence: 57%
“…Amongt hese advantagesa re the impact on the overpotential, [8][9][10] the competing hydrogen evolutionr eaction (HER), [11][12] the product selectivity, [13][14] and the product scope. [15][16][17][18] Especially,I Ls featuring imidazolium cations have emergeda sv ersatile co-catalysts. The activation of CO 2 in these systems is believed to proceed throughn ucleophilic-heterocyclic-carbenes (NHC) generated in situ.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis has been verified by Chang and co‐workers, using N‐heterocyclic carbene with further modification on molecular structure (Figure b). Other relevant studies have been reported as well, such as Wallace et al, Wang and co‐workers, and Tamura et al…”
Section: Recent Advances Of Electrocatalysts For Improved Performancementioning
confidence: 77%
“…This hypothesis has been verified by Chang and co-workers, using N-heterocyclic carbene with further modification on molecular structure (Figure 9b). Other relevant studies have been reported as well, such as Wallace et al, [34] Wang and co-workers, [91] and Tamura et al [92] Besides, Sargent and co-workers [18] theoretically calculated that K + ions adsorbed on local sites of Au surfaces could significantly lower the energy barriers of activation for CO 2 to CO. Moreover, they also identify the tip part of needle-like Au with high radius of curvature could generate high electric field, leading to strengthen adsorption of K + ions at tip parts of Au needles (Figure 9c-f).…”
Section: Surface Modificationmentioning
confidence: 99%